Overexpression of GUCY1A2 Correlates With Poor Prognosis in Gastric Cancer Patients - Li, Xin; Chen, Xiaowei; Hu, Xueju; Shen, Yan; Xu, Rui; Wu, Leilei; Shen, Xiaobing (Frontiers in Oncology, 2021)
Background: Nitric oxide (NO) and cyclic guanosine phosphate (cGMP) play important roles in blood pressure regulation, neurotransmitter delivery, renal function, and tumorigenesis and development. The intermediate link of this signaling pathway, soluble guanylyl cyclase (sGC), is particularly important. However, the role of the GUCY1A2 gene encoding the sGC α2 subunit is unknown. Methods: Gene expression and clinical data were obtained from The Cancer Genome Atlas (TCGA) database. After screening for GUCY1A2 expression, the expression differences between gastric cancer (GC) tissues and adjacent noncancerous tissues were determined using R software. Quantitative real-time polymerase chain reaction (qRT-PCR) and meta-analysis were used to verify the result. The correlation between the expression of GUCY1A2 and clinicopathological parameters was explored by logistic regression. Then, Kaplan-Meier survival analysis and the Cox proportional hazards regression were used to evaluate the relationship between the expression of GUCY1A2 and the survival of GC patients. Finally, gene set enrichment analysis (GSEA) was used to explore and analyze the GC-related signaling pathways affected by high GUCY1A2 expression. Results: We found that GUCY1A2 was highly expressed in GC tissues compared to adjacent noncancerous tissues (P < 0.001). qRT-PCR (P < 0.001) and meta-analysis (SMD = 0.65, 95% CI: 0.20-1.10) confirmed the diﬀerence in GUCY1A2 expression. Logistic regression analysis showed that high expression of GUCY1A2 was associated with histological grade (OR=1.873 for poor vs. well or moderate, P = 0.004) and T stage (OR = 3.389 for T3 vs. T1, P = 0.025; OR = 3.422 for T4 vs. T1, P = 0.028). Kaplan-Meier curves indicated that GC patients with high expression of GUCY1A2 had a poor prognosis than that of patients with low expression. Univariate analysis indicated that GUCY1A2 and some clinicopathological parameters, such as age, pathological stage, and TNM stage, may predict poor prognosis. Multivariate analysis further confirmed that GUCY1A2 was an independent prognostic marker (HR = 1.699; 95%CI, 1.175-2.456; P = 0.005). GSEA showed that the high GUCY1A2 phenotype is significantly enriched for tumor-associated signaling pathways. Conclusions: GUCY1A2 is highly expressed in GC and may be used as a potential prognostic marker.